Utilizing the PDSA Cycle to Achieve Optimal Bed Utilization and Improve the Efficiency of a Chemotherapy Day Care Unit - Asma Pathan; Manjiri Joshi; Karishma Sugandhi; Vinod K. Ramani; Ravi Kannan; Odette Sprujit; Shirley Lewis (SAGE Publishing, 2024)
Introduction Chemotherapy daycare units (CDU) routinely face difficulties, given the waiting time and work pressure. The study objectives include determining the feasibility of a multidisciplinary intervention in facilitating the growth in CDU bed utilization by ∼20%. Methods The quasi-experimental study was conducted during the period 1st May 2021 to 28th February 2022. The strategies of the healthcare improvement project are structured as per the Plan-Do-Study-Act (PDSA) cycle. 'Lean thinking' approach using the A3 sheet tool was applied, as its focus is on organization of processes. Benchmarking technique was used to attain more insight into the optimal performance levels. Results Plan phase: The tracks of CDU process were mapped using the 'process flow diagram' technique. The reasons for the perceived bed shortage and high work pressure were revealed by the Root cause analysis, which includes the 21 prioritized problem areas. Do phase: Various interventions were implemented in the domains of communication systems, developing standard operating protocols and human resource management. Study phase: 9 of the total 21 problem areas were cumulatively responsible for ∼80% of underutilization of CDU beds. Act phase: The planned intervention resulted in an increase in the proportion of CDU bed utilization from 60% (18-20 patients/day) to 75% (23-25 patients/day). Conclusion The PDSA cycle offered optimal structure to this efficiency improvement initiative. The project outcomes were enhanced by the combination of approaches such as lean thinking and benchmarking.